Sistem Pendukung Keputusan Sistem Pendukung Keputusan Penerima Bantuan Program Keluarga Harapan (PKH) Menggunakan Metode Simple Additive Weighting Di Desa Pasirukem: Metode Simple Additive Weighting - Surya, Anggie Dinda Surya; Yana, Adelia Alvi (Informatics and Computer Engineering Journal, 2022)
Program Keluarga Harapan or commonly called PKH is one of the government's programs, namely by providing assistance to Poor Families as poverty alleviation in Indonesia. PKH has been implemented since 2007 and is a Social Protection Program known internationally as Conditional Cash Transfer (CCT). In its implementation, the government needs to select families who are eligible for the program assistance, in the process there are still errors in determining the target families who are eligible to receive the PKH program. The Decision Support System can be a solution so that the beneficiaries of the PKH program are poor families who are on target. With the Simple Additive Weighting (SAW) method as the calculation which is a weighted addition method. Based on the results of calculations ranging from normalization to the ranking process, where from this value the highest to lowest alternative will be taken as a determination for prospective PKH recipients in Pasirukem Village. From this process, the highest ranking results with a value of 9.125 on behalf of Yapi Agil, Hamlet of Wagirsari. The Decision Support System for Recipients of Program Keluarga Harapan Using the Simple Additive Weighting (SAW) Method in Pasirukem Village can help provide decisions to the Village in determining which families will be given social assistance based on the highest score on the ranking results.